EFEKTIVITAS PELAKSANAAN REDISTRIBUSI TANAH DALAM PROGRAM REFORMA AGRARIA DI INDONESIA - Rosa Khairidawati; Novita Ardiani; Asnawi Mubarok (PT. Antis International Publisher, 2024)
This article examines the effectiveness of land redistribution implementation in Indonesia's agrarian reform program. The land redistribution program is part of the government's efforts to achieve equitable land ownership and improve farmers' welfare. This study aims to evaluate the success of the land redistribution program, identify the challenges faced in its implementation, and provide strategic recommendations to enhance the program's effectiveness. The research uses a qualitative method with a case study approach in several regions that focus on land redistribution. Data were collected through in-depth interviews with farmers, government officials, and agrarian experts, as well as field observations and document studies. The findings indicate that while there are some successes in land redistribution, numerous obstacles hinder the program's effectiveness, including complex bureaucracy, agrarian conflicts, and lack of infrastructure support. This article also offers recommendations to overcome these challenges and improve the effectiveness of the land redistribution program in the future.